Improvement of Bearing Capacity of Clay Soil Using Fly Ash - Hasnat, Abul; Ahmed, Safkat Tajwar; Mustafa, Tahmid; Chowdhury, Md. Samiullah (AIUB Journal of Science and Engineering (AJSE), 2020)
The principal aim of the study is to improve the engineering properties of the soil sample using fly ash as a binding material. Bangladeshi fly ash was used in this study. Effects of fly ash on physical and mechanical properties of soil (Atterberg limits, moisture-density relationship, and unconfined compressive strength) are evaluated in the presence of 0%, 2%, 4%, 5%, 8%, 10%, 15%, 20% & 25% fly ash. For understanding the improvement of engineering properties of soil, a parametric analysis is conducted to determine the allowable bearing capacity, settlement and the time required for the consolidation. The allowable bearing capacity is evaluated using several equations for both saturated and unsaturated conditions. It is found that for 5% fly ash content, the maximum allowable bearing capacity is achieved. The maximum value of allowable bearing capacity is 660.12 kN/m2 in the unsaturated condition. The increment of maximum allowable bearing capacity is 77.74% for 5% fly ash content. The lowest value of the settlement was 336 mm (saturated) and 183 mm (unsaturated) for 25% fly ash content. Considering normally consolidated soil, it is found that the least time required for consolidation is 3.19 years for 25% fly ash content.